Causes of multidrug-resistant tuberculosis from the perspectives of health providers: - Souza, Ludmilla Leidianne Limirio (2022)
Funding Information: The study was supported by the São Paulo Research Foundation (FAPESP) [Grant 2018/14337–0], the National Council for Scientific and Technological Development (CNPq) [Grant 130160/2020–2] and Research Productivity Grant from the National Council for Scientific and Technological Development (CNPq) [Grant 304483/2018–4 - PQ modality (Level 1C)]. Publisher Copyright: © 2021, The Author(s).